Mendelian Randomization Studies Do Not Support a Role for Vitamin D in Coronary Artery Disease. (August 2016) - Manousaki, Despoina; Mokry, Lauren E.; Ross, Stephanie; Goltzman, David; Richards, J. Brent
Abstract : Background—: Observational studies support a possible association between decreased vitamin D levels and risk of coronary artery disease (CAD); however, it remains unclear whether this relationship is causal. We aimed to evaluate whether genetically lowered vitamin D levels influence the risk of CAD using a Mendelian randomization approach. Methods and Results—: In this 2-stage Mendelian randomization study, we first identified single-nucleotide polymorphisms associated with 25-hydroxyvitamin D (25OHD) levels in the SUNLIGHT consortium (n=33 996), then tested them for possible violation of Mendelian randomization assumptions. A count of risk alleles was tested for association with 25OHD levels in a separate cohort (n=2347). Alleles were weighted by their relative effect on 25OHD and tested for their combined effect on CAD in the Coronary Artery Disease Genome-Wide Replication and Meta-Analysis (CARDIoGRAM) study (22 233 cases/64 762 controls). Four single-nucleotide polymorphisms were identified to be associated with 25OHD levels, all in or near genes implicated in 25OHD synthesis, transport or metabolism. A count of these risk alleles was strongly associated with 25OHD (n=2347, F -test statistic=49.7, P =2×10 −12 ). None of the single-nucleotide polymorphisms associated with 25OHD levels were associated with CAD (all P values >0.6). The Mendelian randomization odds ratio (OR) for CAD was 0.99 (95% confidence interval, 0.84–1.17; P =0.93; I 2 =0) per SD decrease in log-transformed 25OHD levels. These results persisted after sensitivity analyses for population stratification and pleiotropy. Conclusions—: Genetically lowered 25OHD levels were not associated with increased risk of CAD in a large, well-powered study, suggesting that previous associations between circulating 25OHD levels and CAD are possibly confounded or due to reverse causation. Abstract : Supplemental Digital Content is available in the text.